HDAC6 is a Regulator of CTL Function through Control of Lytic Granule Dynamics - Nunez-Andrade, Norman (Single Cell Biol, 2016)
Viral infections involve specific stress exposure that can influence the quality and average lifespan of an organism. The immune system acts through virus clearance from the organism. Many aspects of immune cells accounting for this response are still under study. Here, we review recent aspects of the molecular mechanisms involved in the delivery of the lethal hit by Cytotoxic T lymphocytes.